One Case of Tuberculosis-Like Leprosy with a Type I Leprosy Reaction - Li J; Wang CH; Yu DH; He Q; He W (Dove Medical Press, 2023)
Jie Li,1,* Chun-Hong Wang,2,* De-Hou Yu,2 Qin He,2 Wei He1 1Department of Dermatology, GuiQian International General Hospital, Guiyang, Guizhou, 550018, People's Republic of China; 2Department of Dermatology, The Affiliated Hospital of Guizhou University, Guiyang, Guizhou, 550001, People's Republic of China*These authors contributed equally to this workCorrespondence: Qin He, Department of Dermatology, The Affiliated Hospital of Guizhou University, No. 28, Guiyi Street, Guiyang, Guizhou, 550001, People's Republic of China, Tel +86 18585037228, Email Heqin_230215@163.com Wei He, Department of Dermatology, GuiQian International General Hospital, No. 1, Dongfeng Street, Wudang District, Guiyang, Guizhou, 550018, People's Republic of China, Email Wei_he66@21cn.comAbstract: Leprosy is a chronic infectious disease primarily affecting the skin and peripheral nerves and is caused by Mycobacterium leprae. Although effective control measures have significantly reduced its global incidence in recent years, its insidious onset and diverse skin manifestations pose considerable challenges to early diagnosis, particularly among young medical practitioners. This study reports a case of tuberculoid leprosy accompanied by a type I reaction (T1R) to leprosy, aiming to contribute to the broader understanding and management of the disease. The patient came from a leprosy-endemic region and had a family history of leprosy. They first presented with neuritis, characterised by numbness in the left upper limb, which is an early-stage symptom often overlooked. This case accentuates the importance of comprehensive examination techniques, including bacteriological and histological investigations, ultrasound and magnetic resonance imaging, to identify early nerve damage, which is critical for prompt diagnosis and intervention. According to World Health Organization data, approximately 200,000 new cases of leprosy are reported worldwide each year, with a prevalence rate of 0.2 cases per 10,000 individuals. The disease exhibits two clinical forms based on the host's immune response: tuberculoid leprosy in a well-immunised population and lepromatous leprosy in a poorly immunised host. The patient in this study demonstrated signs of tuberculoid leprosy, marked by isolated skin papules and plaques, and a T1R, a tissue-destructive, immune-driven inflammatory process. This case underscores the need for ongoing education and updated diagnostic tools to facilitate the early detection of leprosy, particularly in endemic areas. Moreover, attention must be given to the comprehensive care of patients, encompassing both physical and psychological aspects, to improve their quality of life and mitigate social discrimination and prejudice.Keywords: leprosy, tuberculoid leprosy, leprosy reaction